2016
DOI: 10.1039/c6py00605a
|View full text |Cite
|
Sign up to set email alerts
|

Z-type and R-type macro-RAFT agents in RAFT dispersion polymerization – another mechanism perspective on PISA

Abstract: The location of RAFT groups plays a key role for the living polymerization process and the formation of nano-objects in RAFT dispersion polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…A key point is the ability of both blocks to form the so-called microphase-separated domains on a nanoscale level driven by their polarity difference, i.e., the difference in their mixing parameter χ. For this, block copolymers were obtained by first polymerizing the macromonomers VBmPEOz , which feature a styrene-functionalized mPEOz chain, using DDMAT as a RAFT agent to achieve perfect control over the radical polymerization (Scheme ). Consequently, a macro-RAFT agent based on styrene repeating units with grafted PEO side chains was obtained ( PVBmPEOz ). Subsequently, PVBmPEOz was used for the chain extension with styrene to eventually obtain the block copolymer PVBmPEOz- b -PS (hereinafter denoted as BPz) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…A key point is the ability of both blocks to form the so-called microphase-separated domains on a nanoscale level driven by their polarity difference, i.e., the difference in their mixing parameter χ. For this, block copolymers were obtained by first polymerizing the macromonomers VBmPEOz , which feature a styrene-functionalized mPEOz chain, using DDMAT as a RAFT agent to achieve perfect control over the radical polymerization (Scheme ). Consequently, a macro-RAFT agent based on styrene repeating units with grafted PEO side chains was obtained ( PVBmPEOz ). Subsequently, PVBmPEOz was used for the chain extension with styrene to eventually obtain the block copolymer PVBmPEOz- b -PS (hereinafter denoted as BPz) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Also very active over the last 3 years was the group of Tan at Guangdong University (China) that reported dispersion photo-PISA in methanol/water mixtures (isobornyl acrylate [209,210] and MMA [211] for chain extension) and in water (2-hydroxylpropyl methacrylate [212][213][214][215]) as depicted in Fig. 29).…”
Section: Adaptation To Photoinitiationmentioning
confidence: 99%
“…Another advantage of diblock copolymer nano-objects prepared via the Z-RAFT-mediated photo-PISA is that the corona block and the core-forming block can be cleaved easily by removing the trithiocarbonate group (see Figure a). This feature enables the preparation of stabilizer-free nanoparticles and hollow nanomaterials. , Treating RAFT-derived polymers with excess initiator is a common strategy to remove the RAFT reactive group . Herein, mPEG 45 -P t BA 209 vesicles (prepared at 30% w/w t BA concentration) were treated with 50-fold SPTP via the exposure of 405 nm visible light for 5 h. Precipitation occurred during this process due to the absence of stabilizer on the particle surface.…”
mentioning
confidence: 99%
“…37 When using a Z-type macro-CTA, the RAFT reactive groups located on the particle surface do not have access to control the polymerization inside, leading to a certain degree of uncontrolled polymerization. For example, the Zeng group and us 38 recently reported that the use of a Z-type macro-CTA for thermally initiated PISA of styrene only led to the formation of polydisperse micron-sized particles with broad molar mass distributions (M w /M n > 2.80).…”
mentioning
confidence: 99%